Phenotypic characterisation and drug sensitivity testing of mycobacteria isolated from extra-pulmonary tuberculosis - Gurung, R; Bhattacharya, SK; Pradhan, B; Gurung, S; Singh, YI (Kathmandu University Medical Journal, 2010)
Background: Tuberculosis (TB) is a major cause of morbidity and mortality globally, with most cases occurring in developing countries. The importance of extra pulmonary tuberculosis (EPTB) among all forms of tuberculosis has not yet been ascertained in developing countries Objective: To identify and perform phenotypic characterization of clinically important mycobacterium isolates from extra-pulmonary sites along with drug susceptibility testing. Materials and methods: A total of 513 specimens from patients of (EPTB) with varied presentation were studied. Speciation and characterization of isolates were done on the basis of growth and biochemical characteristics. Drug susceptibility testing for mycobacterium isolates was done by proportion method. Results: Fifty four patients clinically suspected to have extra-pulmonary tuberculosis were culture positive for mycobacteria. On characterization 48 of the 54 isolates were identified as M. tuberculosis, 4 as M. bovis and 2 were M. avium/ intracelulare. Drug susceptibility testing was done for the both M. tuberculosis as well as M. bovis. In single drug resistance, Streptomycin was highest followed by Isoniazid, Ethambutol and Refampicin. Multi drug resistance (MDR) was found in 6 isolates and it was observed only in group I cases. Conclusion: EPTB accounts for 10-15 percent of all cases of tuberculosis. Mycobacterium was present in 10.5 percent samples. 48 isolates out of 54 samples were found to be M. tuberculosis. The maximum numbers of M. tuberculosis were isolated from lymph node aspiration. Key words: Phenotypic characterization; drug susceptibility; extra pulmonary tuberculosis DOI: 10.3126/kumj.v8i1.3223 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 57-61